A research on closed-loop control strategy for single-phase off-grid inverter under abrupt load variation - Yao, Na; Zhang, Zhaoyun; Wang, Zhiping (Manufacturing Technology Journal, 2020)
This paper proposes a control strategy for single-phase off-grid inverter, which integrates the three closed-loop control with the iterative-based RMS algorithm. The inverter circuit is modeled, and simulation experiment and prototype verification are performed on Matlab. The results show that the voltage drop problem caused by an abrupt variation of inverter load is improved greatly owing to the addition of voltage RMS loop. Meanwhile, the application of iterative method enhances the dynamic response performance of the system substantially; and improves the real-timeliness of three closed-loop control. The two complement each other to provide a highly effective, reliable control solution for the single-phase off-grid inverter.
Keywords: Heavy load; Inverter; Iterative algorithm; Three-closed loop control